2019
DOI: 10.46367/iqtishaduna.v8i1.151
|View full text |Cite
|
Sign up to set email alerts
|

Wakaf Produktif Di Malaysia

Abstract: Wakaf dalam doktrin agama Islam merupakan salah satu bentuk ibadah yang syarat nilai, karena selainmengandung dimensi vertikal, juga berdimensi horizontal, yang dalam istilah bahasa yuridis formaldikatakan dengan kata-kata kepentingan ibadah dan keperluan umum. Sebagaimana telah diatur dalam Undang-undang No.1 Akta Pentadbiran Undang-undang Islam (Wilayah-wilayah Persekutuan) 1993 (Akta 505) Bahagian 1 Sek. 2- Tafsiranmenurut peraturan pemerintah bab amanah khairat seksyen 61 wakaf dan nazar. P.U (A) 352/85. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
9
0
5
Order By: Relevance
“…Another study by Rahmany, (2014) emphasized the importance of digital marketing in the marketing strategies of Islamic banks. They found that the use of social media, interactive websites, and mobile banking applications can provide a competitive advantage for Islamic banks in reaching a wider target market and enhancing customer interaction.…”
Section: E Discussionmentioning
confidence: 99%
“…Another study by Rahmany, (2014) emphasized the importance of digital marketing in the marketing strategies of Islamic banks. They found that the use of social media, interactive websites, and mobile banking applications can provide a competitive advantage for Islamic banks in reaching a wider target market and enhancing customer interaction.…”
Section: E Discussionmentioning
confidence: 99%
“…In the realm of Islamic legal epistemology (fiqh), waqf is often defined as the "detention (prevention) of property that can be utilized, without causing its existence to vanish, by not disposing of its substance, and directing it towards permissible concrete purposes." Studies on waqf in Malaysia are usually embedded within the broader coverage of popular family law studies, such as marriage, divorce, adoption, and inheritance laws (Rahmany, 2019).…”
Section: A Brief Overview On Waqf In Indonesia and Malaysiamentioning
confidence: 99%
“…Di negara-negara Afrika dan Asia Barat seperti di Mesir, Kuwait dan Morocco telah diwujudkan kementerian wakaf untuk men-tadbir harta-harta wakaf. Dari dana wakaf, masjid-masjid didirikan, berbagaiaktivitas keislaman dilaksanakan secara terencana (Rahmany, 2019).…”
Section: Pengelolaan Wakaf DI Malaysiaunclassified
“…Yang terkenal juga adalah wakaf perusahaan dengan nama JCorp, Johor Corporation. Dengan demikian perwakafan di Malaysia tidak terbatas hanya dalam bentuk pembangunan masjid semata-mata (Rahmany, 2019). Meskipun begitu, negara Malaysia juga memiliki beberapa hambatan dalam mengelola wakaf, di antaranya: (Fauza, 2015) 1) Masalah perundangan, yaitu adanya ketidakseragaman undang-undang wakaf antara negeri-negeri, yang berimplikasi pada perbedaan dalam pemahaman, tafsiran, tata cara pengeluaran fatwa dan hukum.…”
Section: Pengelolaan Wakaf DI Malaysiaunclassified